Exploiting the miniature inverted-repeat transposable elements insertion polymorphisms as an efficient DNA marker system for genome analysis and evolutionary studies in wheat and related species - Ubi, Benjamin Ewa; Gorafi, Yasir Serag Alnor; Yaakov, Beery; Monden, Yuki; Kashkush, Khalil; Tsujimoto, Hisashi (Frontiers in Plant Science, 2022)
Transposable elements (TEs) constitute 80% of the complex bread wheat genome and contribute significantly to wheat evolution and environmental adaptation. We studied 52 TE insertion polymorphism markers to ascertain their efficiency as a robust DNA marker system for genetic studies in wheat and related species. Significant variation was found in miniature inverted-repeat transposable element (MITE) insertions in relation to ploidy with the highest number of ’full site’ insertions occurring in the hexaploids (32.6 + 3.8), while the tetraploid and diploid progenitors had 22.3 + 0.6 and 15.0 + 3.5 ’full sites’, respectively, which suggested a recent rapid activation of these transposons after the formation of wheat. Constructed phylogenetic trees were consistent with the evolutionary history of these species which clustered mainly according to ploidy and genome types (SS, AA, DD, AABB, and AABBDD). The synthetic hexaploids sub-clustered near the tetraploid species from which they were re-synthesized. Preliminary genotyping in 104 RILs showed predominantly 1:1 segregation for simplex markers, with four of these markers already integrated into our current DArT- and SNP-based linkage map. The MITE insertions also showed stability with no single excision observed. The MITE insertion site polymorphisms uncovered in this study are very promising as high-potential evolutionary markers for genomic studies in wheat.